Microcirculatory assessment of patients under VA-ECMO. Issue 1 (December 2016) - Kara, Atila; Akin, Sakir; dos Reis Miranda, Dinis; Struijs, Ard; Caliskan, Kadir; van Thiel, Robert; Dubois, Eric; de Wilde, Wouter; Zijlstra, Felix; Gommers, Diederik; Ince, Can
Abstract Background Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is an effective technique for providing emergency mechanical circulatory support for patients with cardiogenic shock. VA-ECMO enables a rapid restoration of global systemic organ perfusion, but it has not been found to always show a parallel improvement in the microcirculation. We hypothesized in this study that the response of the microcirculation to the initiation of VA-ECMO might identify patients with increased chances of intensive care unit (ICU) survival. Methods Twenty-four patients were included in this study. Sublingual microcirculation measurements were performed using the CytoCam-IDF (incident dark field) imaging device. Microcirculatory measurements were performed at baseline, after VA-ECMO insertion (T1), 48–72 h after initiation of VA-ECMO (T2), 5–6 days after (T3), 9–10 days after (T4), and within 24 h of VA-ECMO removal. Results Of the 24 patients included in the study population, 15 survived and 9 died while on VA-ECMO. There was no significant difference between the systemic global hemodynamic variables at initiation of VA-ECMO between the survivors and non-survivors. There was, however, a significant difference in the microcirculatory parameters of both small and large vessels at all time points between the survivors and non-survivors. Perfused vessel density (PVD) at baseline (survivor versus non-survivor, 19.21 versus 13.78 mm/mm2, p = 0.001) was able to predict ICU survival on initiation of VA-ECMO; the area under the receiver operating characteristic curve (ROC) was 0.908 (95 % confidence interval 0.772–1.0). Conclusion PVD of the sublingual microcirculation at initiation of VA-ECMO can be used to predict ICU mortality in patients with cardiogenic shock.